Effects of particles moisture, conditioning environment, and heat treatment on the formaldehyde emission of urea formaldehyde-bonded particleboard - Lum, Wei Chen; Lee, Seng Hua; Antov, Petar; Lubis, Muhammad Adly Rahandi; Kristak, Lubos; Hrusovsky, Dominik (Universiti Teknologi MARA (UiTM), 2023)
The initial moisture content (MC) and conditioning environment are among the most important factors that affect the properties as well as formaldehyde emission of particleboard. In this study, a three-layer rubberwood particleboard bonded with urea formaldehyde (UF) resin was prepared. Fine and coarse rubberwood particles with initial MC (of 3, 5, 7, 9 and 11%), respectively, were used to fabricate the three-layer particleboard. The produced particleboard was then evaluated for physical and mechanical properties. It was found that particleboard made with particles with 9% MC had the best properties. In the next phase of the study, this particleboard was chosen and exposed to different conditioning environments. The selected conditioning temperatures were 20 and 30 °C while the relative humidity was 30%, 65% and 100%. The findings suggested that the formaldehyde emission of particleboard increased with increasing conditioning temperature and relative humidity. However, the effect of the previous conditioning was nullified after the samples were re-equilibrated in a setting that served as the control. In order to reduce the formaldehyde emission of the particleboard, the samples were subjected to thermal treatment at 130, 150, 170 and 190 °C. It was found that the formaldehyde emission varied with treatment temperatures. Particleboard with the Super E0 level (≤ 0.3 mg/L) was successfully achieved by samples that were treated at 170 °C.